Skal råvaren i land? - Lars Lund (Copenhagen Business School (CBS), Department of Economics, 2006)
– Processing ashore of raw materials from the fisheries tend intuitively to recommend itself because more creation of value added in this manner should take place in Greenland. However, we observe the opposite tendency: production is shifted aboard on factory trawlers and catches are shipped directly to export markets or may be so after transshipping in e.g. Nuuk. It is shown that this actual development indeed is the prediction of location economics. In the case of unemployment it may be optimal to secure raw materials for processing on plants ashore, an aim that may be achieved via subsidies. The optimality of such policy is discussed using concepts from cost benefit analysis, and it is demonstrated how the shadow price of labor has a crucial role. Shifting to the macro level capacity restrictions on plants and on the labor market are pointed out. The effect of taking raw material ashore is illustrated with a macro production function, which is assumed to have a positive marginal product until the capacity limit is hit. This, however, may take place after the noninflationary augmenting level of employment has been reached. Finally the possibility of alternative and better policies than the one relying on subsidies is touched upon.
hdl:10398/7570
Keywords: H00; 330; Greenland; export market; transshipping